2011
DOI: 10.1136/jech.2010.125195
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of anti-illicit-drug public-service announcements: a systematic review and meta-analysis

Abstract: Existing evidence suggests that the dissemination of anti-illicit-drug PSAs may have a limited impact on the intention to use illicit drugs or the patterns of illicit-drug use among target populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
2
27
0
1
Order By: Relevance
“…Similarly, considerations of peer to peer injection education interventions as potential models of injection prevention may need to be considered [58]. Finally, emerging approaches must not repeat the failures of past prevention efforts, which have unsuccessfully used as a tool to bolster anti-drug social norms [59,60]. Beyond avoiding a repetition of past ineffectiveness, future interventions must also ensure that they do not inadvertently increase the stigma around drug injecting while seeking to prevent this behavior.…”
Section: Barriers To Effectively Preventing Injection Initiationmentioning
confidence: 99%
“…Similarly, considerations of peer to peer injection education interventions as potential models of injection prevention may need to be considered [58]. Finally, emerging approaches must not repeat the failures of past prevention efforts, which have unsuccessfully used as a tool to bolster anti-drug social norms [59,60]. Beyond avoiding a repetition of past ineffectiveness, future interventions must also ensure that they do not inadvertently increase the stigma around drug injecting while seeking to prevent this behavior.…”
Section: Barriers To Effectively Preventing Injection Initiationmentioning
confidence: 99%
“…PSAs can be described as advertisements or commercials that aim to provide information or advice about a particular health or social issue, or promote activities that serve the wider community [2]. …”
Section: Introductionmentioning
confidence: 99%
“…However, evidence has demonstrated that interventions seeking to prevent entry into drug use through social marketing are generally ineffective. 19 This is because anti-drug PSAs generally seek to bolster protective social norms by highlighting the dangers - physical, mental and moral - that arise with the use of drugs, in line with classical approaches to deterrence. 20 This emphasis on fear-based deterrence, however, has been shown to negatively impact intentions to use drugs among PSA audiences.…”
mentioning
confidence: 99%
“…This, in turn, may arouse curiosity among viewers to experiment with drug use and lead to a weakening of protective social norms against their use. 21 The clear failure of such social marketing efforts, evidence in support of which has been generated by both independent experts 19 and government agencies, 22,23 belies a broader issue. Experts have posited that, because of the highly visible nature of these interventions, anti-drug social marketing interventions may have a secondary benefit in bolstering support for policies of drug criminalization through the mass media.…”
mentioning
confidence: 99%